Changes in the abscisic acid content of oat leaves during senescence - Gepstein, Shimon (1980)
To investigate the possibility that experimental promotion of retardation of the senescence of oat leaves may be mediated by abscisic acid (AbA), determinations of AbA were made in leaves senescing under different conditions. The extracts were subjected to thin-layer chromatography, the spots were eluted and esterified, and the AbA was determined by gas chromatography (overall recovery, about 75%). In darkness, where the stomata are closed and senescence is rapid, the concentration of AbA increases to at least 5 times its initial value by the second day, the time when chlorophyll loss is most rapid. In light, where the stomata are open and senescence is very slow, no such increase occurs. But when, in light, the stomata are closed by floating the leaves on 1 M mannitol, the AbA level again increases to about 5 times the initial value; if the stoma response is prevented by kinetin, the increase in AbA is largely suppressed. Similarly, phenylmercuric nitrate, at a concentration that closes the stomata, causes a 4-fold increase in AbA. It is concluded that stomatal closure itself causes AbA accumulation and, thus, that AbA may indeed be the proximal cause of leaf senescence.